Impact of Polycystic Ovary Syndrome (PCOS) on Female Fertility and Metabolic Health - Sobia Hamza, Durre Shawar, Sana Gul, Ambareen Haaris, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: PCOS is one of the widespread endocrine illnesses during the reproductive years in women. It is characterized by the hormonal deficiency, ovulatory imbalance, and disorder of metabolism. PCOS occurs as one of the leading factors of infertility alongside insulin resistance, obesity and the risk of type 2 diabetes, and can occur to both metabolic and reproductive health. Objective: To identify the impact of PCOS on fertility and on metabolic indicators in women and also, to analyses the clinical outcomes of PCOS patient population and control population. Study Design: A cross-sectional study. Place and Duration of Study: The study was Conducted in Department of Gynae & Obs, KTH-MTI Peshawar Khyber Teaching hospital (MTI) Peshawar from June 2022 to july 2023. Methods: A cross-sectional study was done by including a sample of 100 women with PCOS based on the Rotterdam criteria. Hormonal Profile, menstrual history, metabolic parameters, and data on fertility were taken. The controls were matched to the PCOS patients of the same age and analyzed. The results were established using the mean values, standard deviations and p-value in calculating significance in the differences found between groups. Results: The sample to conduct the study was 100 and the average age was 27.5 0 4.2. The androgens present in the serum (p=0.001), indicators of insulin resistance (p=0.002) and body mass index (BMI) (p=0.004) were highly increased in the PCOS patients as compared to controls. Eighty-five per cent of the patients compared to 10 per cent control showed ovulatory dysfunction (p<0.001). There was a very high prevalence of the metabolic syndrome in the PCOS group (p=0.005). Conclusion: In summary: COS reduces female fertility remarkably in terms of hormonal and ovulatory disturbances and is strictly linked with the adverse repercussions on metabolism health. Reproductive and metabolic complications are the other issues that present serious reproductive challenges to the affected women and reproductive care should be carried out early and comprehensively. Keywords: PCOS, Fertility, Metabolic Health, Insulin Resistance